Hubungan Persepsi Lansia Tentang Kematian Dengan Kecemasan Dalam Menghadapi Kematian - Fauziah Irwan; Reni Zulfitri; Jumaini Jumaini (JUKEJ : Jurnal Kesehatan Jompa, 2022)
Older people often focus their attention on death because they experience various declines, especially deterioration of health. Older people tend to experience anxiety, one of which is anxiety about death. The anxiety you feel depends on how a person perceives death itself. These perceptions can be either positive or negative. The purpose of this study is to investigate the relationship between the perception of death and anxiety about death of the elderly in the workplace of the Payung Sekaki health center. Methods: This study uses a correlation design approach in cross-section. The sampling technique in this study was ascheme targeting cluster sampling 98 respondents. A questionnaire adapted from the questionnaire used for perception of death is the Collet Lester-Fear of Death Scale and the Death Anxiety ScaleAnxiety About Death for. Results: The number of respondents with negative perception was 55 (56.1%), 5 had low death anxiety (9.1%), 42 people (76.4%) had moderate anxiety about death, and 8 people had low anxiety about death. people ( 14.5%) had high levels of anxiety about death. 43 people (43.9%) had a positive perception, 10 people (23.3%) said they had low anxiety about death, and 33 people (76.7%) had normal anxiety about death. Conclusion: The perception of death is significantly related to the anxiety about death in the elderly.